Diabetes: vivendo e aprendendo - Queiroz, Reijane Mara Pinheiro; Romero, Elisa Mara Carvalho; Mafra, Luis Cesar; de Sousa, Sulamita; Oliveira, Katilce Xavier (Experiências Exitosas de Farmacêuticos no SUS, 2016)
Diabetes: vivendo e aprendendo